2008
DOI: 10.1001/archneurol.2007.12
|View full text |Cite
|
Sign up to set email alerts
|

Undernutrition as a Predictor of Poor Clinical Outcomes in Acute Ischemic Stroke Patients

Abstract: To determine whether changes in nutritional status in the first week after acute ischemic stroke and undernutrition predicts poor clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
144
2
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(157 citation statements)
references
References 18 publications
4
144
2
7
Order By: Relevance
“…Serum albumin levels decline with age, and the proportion of patients with hypoalbuminemia [16,17], nosocomial infections [18], commensal pneumonia [19], cancer and sepsis [20], and pressure sores [21] has been used as risk factors for death. In recent years, it has been reported that a low serum albumin level is a risk factor for ischemic heart disease [22] and cerebral infarction [23], which greatly influences the prognosis and quality of life of the elderly. Therefore, it is very important to maintain a good nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…Serum albumin levels decline with age, and the proportion of patients with hypoalbuminemia [16,17], nosocomial infections [18], commensal pneumonia [19], cancer and sepsis [20], and pressure sores [21] has been used as risk factors for death. In recent years, it has been reported that a low serum albumin level is a risk factor for ischemic heart disease [22] and cerebral infarction [23], which greatly influences the prognosis and quality of life of the elderly. Therefore, it is very important to maintain a good nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…55 This study unites the knowledge of neurologists, cardiologists, and endocrinologists, and their findings might improve rehabilitation after stroke. Generally, impaired feeding, reduced caloric intake, and loss of appetite lead to a negative nutritional and nitrogen balance, 56,57 and immobilization causes physical inactivity and muscle atrophy after stroke. 58,59 It has been shown that elevated volumes of TNF-α are responsible for muscle loss and that plasma concentrations of the enzyme visfatin were significantly elevated in patients after ischemic stroke.…”
Section: Current Developments On Muscle Mass Lossmentioning
confidence: 99%
“…34 Some reports have shown that premorbid undernutrition was associated with initial stroke severity and poor stroke outcomes. 35, 36 Kim et al reported that ischemic stroke patients with higher body mass index (BMI) were likely to have mild stroke (NIHSS 0-7) at admission. 37 However, data on those factors (ie, lipid profile levels, prior statin use, BMI and the status of nutrition) were not collected in the present study.…”
Section: 001mentioning
confidence: 99%